Palliative care advanced practice nursing in Israel: bridging creation and implementation. (2nd December 2019) - Collett, D.; Feder, S.; Aaron, E.; Haron, Y.; Schulman‐Green, D.
Abstract : Aim: To describe Israel's development of the palliative care advanced practice registered nurse as a foundation for the development of the advanced practice registered nurse role in other specialties. Background: Palliative care centres on alleviating physical, emotional, social and spiritual distress associated with life‐limiting illness. In 2009, Israel introduced the palliative care advanced practice nurse role, that is, registered nurses with specialized training in palliative care, to address increasing palliative care needs. Introduction: While there has been investment in its development, full implementation of the advanced practice nurse has not yet been achieved. Methods: In this qualitative descriptive study, we conducted a document analysis ( n  = 11) and key informant interviews ( n  = 11), extracted themes using qualitative content analysis and triangulated data sets. Results: Documents reflected growing palliative care needs and uniform requirements for advanced practice nurse training. Interviews uncovered a perceived lack of awareness of palliative care, the need for increased role definition and practice authority for advanced practice nurses, and barriers to entry and training for this role. Discussion: Findings highlight ongoing needs in palliative care and advanced practice nursing and a trajectory of growth. Conclusions: The challenges Israel faces in implementation of the palliative care advanced practice nurse role inform development of other advanced practice nursing roles in Israel and other countries. Implications for Nursing Practice: Streamlining training pathways and resolving scope of practice issues will assist in implementation of advanced practice nursing roles. Implications for Health Policy: Our data offer targets for policymakers advocating the advanced practice nurse role, including training requirements and scope of practice.